Healthcare providers' perception of faecal microbiota transplantation with clostridium difficile infection and inflammatory bowel disease: a quantitative systematic review. (September 2021) - Liu, Yanghua; Alnababtah, Kal; Cook, Simon; Yu, Ying
Background: Clostridioides difficile infection (CDI) and inflammatory bowel disease (IBD) are global gastroenterological diseases that cause considerable burden on human health, healthcare systems, and society. Faecal microbiota transplantation (FMT) is an effective treatment for recurrent Clostridioides Difficile Infection (rCDI) and a promising therapy for IBD. However, indication for FMT in IBD is still unofficial. Consequently, the National Institute for Health and Care Excellence (NICE) is seeking healthcare providers' advice on whether to update FMT guidelines. Methods: A systematic review methodology was adopted for this study. Five databases (CINAHL, MEDLINE, Cochrane Library, Scopus, Web of Science) and grey literature were systematically searched for English language literature to 14 May 2021. The quality of the included studies was then appraised using the Institute for Public Health Sciences cross-sectional studies tool, after which the findings of the studies were narratively synthesised. Results: Thirteen cross-sectional studies with 4110 validated questionnaire responses were included. Narrative synthesis found that 39.43% of respondents were familiar with FMT (N = 3746, 95%CI = 37.87%–41%), 58.81% of respondents would recommend FMT to their patients (N = 1141, 95%CI = 55.95%–61.67%), 66.67% of respondents considered lack of clinical evidence was the greatest concern regarding FMT (N = 1941, 95%CI = 64.57%–68.77%), and 40.43% respondents would not implement FMT due to concerns about infection transmission (N = 1128, 95%CI = 37.57%–43.29%). Conclusion: Healthcare providers' knowledge of FMT is relatively low and education is an effective strategy to improve it. As knowledge of FMT increases, willingness to recommend it also increases. Strengthening FMT clinical efficacy and reducing infection can enhance its public acceptance, application and popularity. However, further research is required to explore the donor screening procedure.